PENGARUH RETURN ON ASSETS (ROA) DAN EARNINGS PER SHARE (EPS) TERHADAP RETURN INVESTASI SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Salsabilla Maharani; Azkia Buana Putri Ning Nabila; Keiko Andromeda Ramadhania Azizah; Siti Rahma; Nadiva Putri; Cantika Istiana Putri Nadira; Tias Suningsih (CV. Denasya Smart Publisher, 2026)
This study aims to investigate the impact of Return on Assets (ROA) and Earnings Per Share (EPS) on stock investment returns in entities in the food and beverage sector listed on the Indonesia Stock Exchange for the period 2022 to 2024. The research approach used is quantitative combined with an associative research design. The data used is secondary data taken from financial statemrts and stock prices of the entities. The sampling technique applies purposive sampling with a total of 15 entities as samples. For analysis, a multiple linear regression method is used which includes classical assumption testing, t-test, F-test, and coefficient of determination. The research findings indicate that individually, Return on Assets (ROA) does not have a significant effect on stock returns with a significance value of 0.822. Similarly, Earnings Per Share (EPS) also does not show a significant effect on stock returns with a significance value of 0.121. Simultaneously, ROA and EPS do not have a significant effect on stock returns, with a significance value of 0.351. The results of this study indicate that stock returns in entities in the food and beverage sector are largely influenced by factors other than profitability, such as macroeconomic conditions, inflation rates, interest rates, and market sentiment. This research is expected to serve as a benchmark for investors investment in making decisions and serve as a reference for future research.